2002
DOI: 10.1002/cne.10286
|View full text |Cite
|
Sign up to set email alerts
|

Differential localization of high‐ and low‐molecular‐weight variants of microtubule‐associated protein 2 in the developing rat telencephalon

Abstract: Microtubule-associated protein 2 (MAP2) occurs in developing mammalian neuronal tissue as both high- and low-molecular-weight forms with temporally regulated expression. We studied the MAP2 expression in the developing rat telencephalon with monoclonal antibodies that recognized both the high- and low-molecular-weight forms of MAP2 variants or that specifically recognized high-molecular-weight forms of MAP2 variants. Differences in the staining patterns of these antibodies reflected differences in the distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The monopolar or bipolar morphology of pioneering cortical MAP2-positive neurons is typical of tangentially migrating cells (Tamamaki et al, 1997;Fujimori et al, 2002). The fact that we found similar cells at the level of the ventricular angle and in the intermediate zone of the basal telencephalon (Fig.…”
Section: Pioneer Neurons Of the Human Cortexmentioning
confidence: 49%
See 1 more Smart Citation
“…The monopolar or bipolar morphology of pioneering cortical MAP2-positive neurons is typical of tangentially migrating cells (Tamamaki et al, 1997;Fujimori et al, 2002). The fact that we found similar cells at the level of the ventricular angle and in the intermediate zone of the basal telencephalon (Fig.…”
Section: Pioneer Neurons Of the Human Cortexmentioning
confidence: 49%
“…MAP2 occurs in developing mammalian neuronal tissue as both high-and low-molecular weight forms, with temporally regulated expression (Fujimori et al, 2002). It is much more abundant in cell bodies and dendrites than in axons.…”
Section: Methodsmentioning
confidence: 99%
“…To test this, we performed double-labeling studies of Dlx2 and GABA immunohistochemistry (Fig. 1R) and Dlx2 and MAP2 immunohistochemistry (Fujimori et al, 2002) extensively on the frontal sections of E16 embryo brains and found that more than 88% of the Dlx2-positive cells were neurons. Dlx2-positive oligodendrocyte precursors thus appear to make up less than 12% of Dlx2-positive cells migrating from the GE to the neocortex in the IZ of embryos at E16.…”
Section: Resultsmentioning
confidence: 98%
“…To test this, we performed double‐labeling studies of Dlx2 and GABA immunohistochemistry (Fig. 1R) and Dlx2 and MAP2 immunohistochemistry (Fujimori et al, 2002) extensively on the frontal sections of E16 embryo brains and found that more than 88% of the Dlx2‐positive cells were neurons. Dlx2‐positive oligodendrocyte precursors thus appear to make up less than 12% of Dlx2‐positive cells migrating from the GE to the neocortex in the IZ of embryos at E16.…”
Section: Resultsmentioning
confidence: 99%